2006
DOI: 10.1029/2005jc003129
|View full text |Cite
|
Sign up to set email alerts
|

Decadal variability of the air‐sea CO2 fluxes in the equatorial Pacific Ocean

Abstract: [1] In order to determine the interannual and decadal changes in the air-sea carbon fluxes of the equatorial Pacific, we developed seasonal and interannual relationships between the fugacity of CO 2 (fCO 2 ) and sea surface temperature (SST) from shipboard data that were applied to high-resolution temperature fields deduced from satellite data to obtain high-resolution large-scale estimates of the regional fluxes. The data were gathered on board research ships from November 1981 through June 2004 between 95°W … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

23
233
2

Year Published

2008
2008
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 185 publications
(258 citation statements)
references
References 48 publications
23
233
2
Order By: Relevance
“…One would ask if such a difference is ascribed to the spatial variability (i.e., 125 • W-140 • W vs. 150 • W), the interannual variability (i.e., 1992 vs. 1994), or both? Previous observation and modeling studies have shown large spatial and temporal variations in physical and biogeochemical processes occurring in the equatorial Pacific (Feely et al, 2002(Feely et al, , 2006Chavez et al, 1999;Murtugudde et al, 1999;Wang et al, 2006a, b). However, little is known about the large scale spatial and temporal variations of DON and PON in the equatorial Pacific.…”
Section: Introductionmentioning
confidence: 99%
“…One would ask if such a difference is ascribed to the spatial variability (i.e., 125 • W-140 • W vs. 150 • W), the interannual variability (i.e., 1992 vs. 1994), or both? Previous observation and modeling studies have shown large spatial and temporal variations in physical and biogeochemical processes occurring in the equatorial Pacific (Feely et al, 2002(Feely et al, , 2006Chavez et al, 1999;Murtugudde et al, 1999;Wang et al, 2006a, b). However, little is known about the large scale spatial and temporal variations of DON and PON in the equatorial Pacific.…”
Section: Introductionmentioning
confidence: 99%
“…[2] Long-term increases of CO 2 levels in seawater and the atmosphere have been observed in various oceanic zones such as subtropical North Pacific and North Atlantic [e.g., Inoue et al, 1995;Midorikawa et al, 2005;Takahashi et al, 2006;Bates, 2007;Dore et al, 2009], the equatorial Pacific [e.g., Feely et al, 2006;Ishii et al, 2009], subarctic North Pacific and North Atlantic [e.g., Schuster et al, 2009;Metzl et al, 2010;Wakita et al, 2010;Wong et al, 2010] and the Southern Ocean Metzl, 2009]. Although it is important to understand the changes in ocean circulation, biogeochemical processes and their roles in changing oceanic CO 2 levels, the longterm CO 2 increase in the ocean is predominantly attributable to the absorption of CO 2 that is rapidly increasing in the atmosphere, primarily as a result of human activities such as fossil fuel combustion and land-use changes.…”
Section: Introductionmentioning
confidence: 99%
“…During El Niño conditions, the warm pool expands considerably and the thermocline deepens in the eastern Pacific, both leading to a reduction of the equatorial outgassing of CO 2 to the atmosphere, so that there is a strong El Niño/La Niña signal in the resulting CO 2 fluxes. Feely et al [17] also identified a change in regime which they associated with the changing phase of the Pacific Decadal Oscillation (PDO), evident when comparing periods before 1986 and after 1990. Before this transition, the region seems to have been a slowly decreasing source of CO 2 to the atmosphere, with the surface pCO 2 changing little while atmospheric CO 2 rose steadily.…”
Section: Is the Sink Increasing Or Decreasing?mentioning
confidence: 99%
“…We briefly describe these regional time series below. [17]. In addition to the TAO-related observations, the equatorial Pacific has been the focus of many oceanographic studies during the Joint Global Ocean Flux Study (JGOFS) era (e.g.…”
Section: Is the Sink Increasing Or Decreasing?mentioning
confidence: 99%